2022
DOI: 10.3390/medicina58091219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of McConnell and Kinesio Tapings on Pain and Gait Parameters during Stair Ambulation in Patients with Patellofemoral Pain Syndrome

Abstract: Background and Objectives: The purpose of this study was to investigate the effects of McConnell and Kinesio tapings on knee pain and gait parameters during stair ambulation in patients with patellofemoral pain syndrome (PFPS). Materials and Methods: We selected 52 young adults suffering from anterior knee pain due to PFPS to participate. Then, we randomly assigned 26 patients to either the McConnell or the Kinesio taping groups. We measured their knee pain and gait parameters during stair ambulation before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…After exclusion criteria were applied, 14 randomized controlled trials (RCTs) investigating the efficacy of intramuscular patches for treating PFPS were ultimately included. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Additional studies were not found through reviewing articles and references included in the study. Both researchers concurred during the literature search and inclusion process.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…After exclusion criteria were applied, 14 randomized controlled trials (RCTs) investigating the efficacy of intramuscular patches for treating PFPS were ultimately included. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Additional studies were not found through reviewing articles and references included in the study. Both researchers concurred during the literature search and inclusion process.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…The features of the investigations included are presented in Table 1. A sum of 14 randomized controlled studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35] were integrated, comprising 9 in English and 5 in Chinese. In the experimental group, 4 studies utilized KTs alone, [27,29,31,35] while 6 studies combined KTs with exercise therapy.…”
Section: Basic Characteristics and Quality Assessment Of Included Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kinesio taping (KT) is the application of an adhesive elastic tape, which has been widely used in the field of sports medicine because of its advantages of economic convenience and noninvasiveness [ 15 ]. KT can be stretched by 130%–150%, and the elastic recoil in KT lifts the skin and increases the space between skin and muscle [ 16 ]. The tension provided by KT can increase blood circulation and lymphatic drainage, and reduce the pressure of swelling on subcutaneous pain receptors, thus relieving pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%